OPTIMALISASI TUGAS CAMAT DALAM IMPLEMENTASI KEBIJAKAN OTONOMI DAERAH DI DISTRIK MIMIKA TIMUR KABUPATEN MIMIKA - PEKEY, ANSELMUS; RUMAPEA, PATAR; DENGO, SALMIN (JURNAL ADMINISTRASI PUBLIK, 2014)
ABSTRACT : The position of sub-district for the implementation of decentralization policy is different from the unit area perangl at other districts in the region, as well as organizing public administration tasks, sub-districtal so has the task of dealing with the affairs of local autonomy meaning ful community service delegated by the Regents. The purpose of this study is to determine how to optimize the assignment subdistrict/district chief in the implementation of regional autonomy policy in East Mimika district. The research method used was a qualitative method. Informants in this study as many as 14 people were taken from the district government elements (4 people), the element leader/officer UPT Department/Agency Regions (3), the village government elements (3), elements of traditional leaders (1 person), elements of character religion(1 person), farmers elements (1) and elements of micro driver (1 person), research instrument is the researcher's own, while collecting data using interview techniques. Data analysis was performed with qualitative analysis techniques interactive model of Miles and Hubernann. The results showed: (1) Task district chief in the administration of general governance can already be implemented with effective and efficient, but not all optimal; (2) The task of the district chief in handling the affairs of regional autonomy under the authority of the government district or delegated by there gents meaning ful community service also has to be implemented with effective and efficient butn ot optimal(3) barriers or major obstacles in the optimization task of the head of the districtitis the human resource factor/in adequate government employees, as well as factors supporting infrastructure and facilities in a dequatetask execution, and budget/funds are not sufficient. Based on the research results of optimizing task be concluded that the District Head/Head of the District in the implementation of the decentralization policy has not all be true,but generally is quite effective and efficient; in other words, the task ofthe head of the district in the implementation of regional autonomy policy, not all can be implemented optimally, but generally is quite effective and efficient. Keywords: optimizationtaskssubdistrict head/districthead, the implementation ofregional autonomypolicy.